Implementing Kahoot-assisted Team-Assisted Individualization (TAI) Cooperative Learning on Mathematics Problem-Solving Skills and Self-Confidence in Junior High School Students - Vina Pebrianti (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2025)
This study aims to determine the effect of the Team Assisted Individualization (TAI) cooperative learning model assisted by Kahoot on students' mathematical problem-solving abilities and self-confidence. The method used is a mixed method, with an embedded model design. The research subjects were 8th-grade students at SMP Pasundan 3 Bandung. The instruments used were problem-solving ability tests and a Likert-scale self-confidence questionnaire. The results indicated that students who learned through the Kahoot-assisted TAI model experienced significantly greater improvements in mathematical problem-solving skills and self-confidence than those who received conventional instruction. These results indicate that integrating cooperative learning with a gamified digital platform can effectively enhance students' cognitive and affective learning outcomes.